2019
DOI: 10.1186/s13018-019-1144-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tranexamic acid on the recovery of osteochondral defects treated by microfracture and acellular matrix scaffold: an experimental study

Abstract: Background Microfracture and scaffold application in the treatment of osteochondral defects is still one of the most frequently used methods in the clinic. The most important step in this treatment method is the stabilization of fibrin clot. Tranexamic acid (TA) is an antifibrinolytic agent commonly used in orthopedic surgery in recent years. This study evaluated the effect of local TA application on healing of experimentally induced osteochondral defects on rabbits. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…111 In animal models, fibrin glue containing tranexamic acid gave fewer intraabdominal adhesions, 112,113 and topical tranexamic acid reduced healing in tendons 114 but increased healing in fractures. 115,116 The plethora of processes involving plasminogen/ plasmin/urokinase-type plasminogen activator warrants further investigations regarding potential adverse and beneficial effects of topical tranexamic acid.…”
Section: Local Adverse Effects After Local Use?mentioning
confidence: 99%
“…111 In animal models, fibrin glue containing tranexamic acid gave fewer intraabdominal adhesions, 112,113 and topical tranexamic acid reduced healing in tendons 114 but increased healing in fractures. 115,116 The plethora of processes involving plasminogen/ plasmin/urokinase-type plasminogen activator warrants further investigations regarding potential adverse and beneficial effects of topical tranexamic acid.…”
Section: Local Adverse Effects After Local Use?mentioning
confidence: 99%
“…In that study, they found that TXA treatment had no side effects on the final quality of osteochondral reparative tissue but may shorten the modulation to fibrocartilage tissue. In another study, Degirmenci et al evaluated the effect of intra-articular TXA application on the recovery of experimentally induced osteochondral defects in rabbits [ 14 ]. In that study, the rabbits were divided into two groups: Group 1 (study group) and Group 2 (control group).…”
Section: Discussionmentioning
confidence: 99%
“…TXA was supported as a safe drug for topical use in a few studies (Table 1 ). In the study of Degirmenci et al [ 1 ], an in vivo study on experimental animals, TXA seemed to have a significant contribution to the healing of osteochondral defects. This was observed not only macroscopically but also histopathologically, where samples treated with TXA had clearly better recovery than the control groups.…”
Section: Txa Administration and Safe Levelsmentioning
confidence: 99%
“…Tranexamic acid (TXA) is an antifibrinolytic agent and a synthetic derivative of the amino acid lysine, which can inhibit the activation of plasminogen and the fibrin breakdown process[ 1 ]. Plasminogen is a glycoprotein pro-enzyme which is produced in the liver.…”
Section: Introductionmentioning
confidence: 99%